Stability of Coinage Metals Interacting with C60 - Kuganathan, N.; Srikaran, R.; Chroneos, A. (Nanomaterials, 2019)
: Buckminsterfullerene (C60) has been advocated as a perfect candidate material for the encapsulation and adsorption of a variety of metals and the resultant metallofullerenes have been considered for the use in different scientific, technological and medical areas. Using spin-polarized density functional theory together with dispersion correction, we examine the stability and electronic structures of endohedral and exohedral complexes formed between coinage metals (Cu, Ag and Au) and both non-defective and defective C60. Encapsulation is exoergic in both forms of C60 and their encapsulation energies are almost the same. Exohedral adsorption of all three metals is stronger than that of endohedral encapsulation in the non-defective C60. Structures and the stability of atoms interacting with an outer surface of a defective C60 are also discussed. As the atoms are stable both inside and outside the C60, the resultant complexes can be of interest in different scientific and medical fields. Furthermore, all complexes exhibit magnetic moments, inferring that they can be used as spintronic materials.
Keywords: C60; Copper; Silver; Gold; Encapsulation energy